Homemade Candy Plug Using a Zenith Alpha Thoracic Stent-Graft for False Lumen Distal Occlusion in Acute-on-Chronic Type B Aortic Dissection. (October 2019) - Yap, Kok Hooi; Tham, Yi Chuan; Tay, Kiang Hiong; Tze Tec, Chong; Irani, Farah Gillan; Kian, Ch'ng Jack; Chao, Victor T. T.
Purpose: To report a candy-plug technique using a Zenith Alpha stent-graft to occlude the distal false lumen in a patient with a complicated chronic type B aortic dissection.Case Report: A 50-year-old male smoker presented with chest pain due to rapidly growing complicated chronic type B aortic dissection. Computed tomography angiography (CTA) showed the dissection extending from distal to the origin of the left subclavian artery (LSA) down to the left femoral artery. There was fusiform aneurysmal dilatation of the proximal descending aorta measuring up to 5.8 cm in diameter. He underwent left carotid–subclavian artery bypass, thoracic endovascular aortic repair with a Zenith Alpha stent-graft, a left common carotid artery chimney, and embolization of the proximal LSA. Serial CTA showed persistent false lumen flow. A decision was made to occlude the distal large false lumen using the candy-plug technique. A 44×125-mm Zenith Alpha stent-graft was used to prepare the candy plug. A gutter leak and a type Ia endoleak were embolized via a left brachial artery approach. At 2.5 years, imaging showed the candy plug in position, no endoleak, and the thrombosed false lumen in the thoracic aorta reduced in size.Conclusion: The candy-plug technique is useful in facilitating complete occlusion of the false lumen in chronic aortic dissection, which avoids an open procedure and the risk of higher morbidity.